Membránový lis - Krčál, Zdeněk (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2010)
Cílem této diplomové práce je konstrukční návrh membránového lisu pro tváření termoplastů. Lis je rozdělen na dvě komory. První komora je určena pro tváření polotovaru na tvářecí teplotu a druhá komora je určena pro ohřev polotovaru. Teoretická část diplomové práce je zaměřena používaným technologiím a popisu tvarování plastů. V praktické části diplomové práce je detailně rozpracován návrh lisu včetně pevnostních výpočtů a výpočtů pohonných jednotek. Celý návrh, včetně jednotlivých částí, je provedený v programu Autodesk Inventor. V závěru práce je uvedena ekonomická a bezpečnostní analýza.

The aim of this thesis is constructional concept of diaphragm press for thermoplastic forming. The press consists of two chambers. First chamber is designed for forming of semi-finished product to forming temperature and second chamber is designed for heating the semi-finished product. Theoretical part of this thesis is focused on technologies in use and shaping of plastic description. Practical part of this thesis deals with detailed description of press concept including consistence calculations and drive units calculations. The whole concept, including its individual parts, is designed using the Autodesk Inventor software. At the end of this thesis, there is the economic and safety analysis.
Diaphragm Press
Keywords: Plošné tváření; lisování plastů; konstrukce strojů; vakuum.; Areal forming; pressing of plastics; construction of machines; vacuum.